Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum Ina Gelekat Kabupaten Flores Timur - Melania Bare Hurint; Yosefina Andia Dekrita; Maria Silvana Mariabel Carcia (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This research aimed to determine and assess the financial performance of Ina Gelekat Regional Water Supply in East Flores Regency in 2018-2022 besed on financial ratio measurement tools that refer to the Decree of the Minister of Home Affairs Number 47 of 1999. The type of data was quantitative data. Data collection methods were casrried out by literauture review, direct observation, and interview. Data analysis techniques used financial performance analysis with ten financial ratios based on the Decree of the Minister of home Affairs Number 47 of 1999, regarding guidelines for assessing the financial performance of the Municipal Water Works of East Flores Regency in 2018-2022 following the Decree of the Minister of Home Affairs Number 47 of 1999. The results showed that in 2018 it produceced the “ Excellent” category with a financial performance value of 51.33, in 2019 it produced the “Excellent” category with a financial performance value of 51.33, in 2020 it produced the “ Excellent” category with a financial performance value of 56.67, in 2021 it produced the “ Exellent” cetegory with a financial performance value of 63.33, and in 2022 it produced “ Exellent” category with a financial performance value of 61.67.